2023
DOI: 10.3389/fmicb.2023.1184387
|View full text |Cite
|
Sign up to set email alerts
|

Assessing phenotypic virulence of Salmonella enterica across serovars and sources

Abstract: IntroductionWhole genome sequencing (WGS) is increasingly used for characterizing foodborne pathogens and it has become a standard typing technique for surveillance and research purposes. WGS data can help assessing microbial risks and defining risk mitigating strategies for foodborne pathogens, including Salmonella enterica.MethodsTo test the hypothesis that (combinations of) different genes can predict the probability of infection [P(inf)] given exposure to a certain pathogen strain, we determined P(inf) bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…To further complicate this situation, several studies have demonstrated that control strategies based on ‘serovars’ without consideration of the actual pathogenic potential of the single strain, as is promoted by the current EU legislation, might overlook highly pathogenic Salmonella strains, which do not necessarily belong to the target serovars. Such strains could spread as emerging clones, becoming potential causes of new outbreaks (Petrin et al., 2023 ). Unfortunately, so far, the identification of virulence patterns to unambiguously predict Salmonella pathogenicity in different hosts still remains very challenging.…”
Section: Discussionmentioning
confidence: 99%
“…To further complicate this situation, several studies have demonstrated that control strategies based on ‘serovars’ without consideration of the actual pathogenic potential of the single strain, as is promoted by the current EU legislation, might overlook highly pathogenic Salmonella strains, which do not necessarily belong to the target serovars. Such strains could spread as emerging clones, becoming potential causes of new outbreaks (Petrin et al., 2023 ). Unfortunately, so far, the identification of virulence patterns to unambiguously predict Salmonella pathogenicity in different hosts still remains very challenging.…”
Section: Discussionmentioning
confidence: 99%
“…However, all 102 strains were successfully sequenced. Consequently, all 102 strains were utilized for the further antimicrobial susceptibility testing and whole genomic sequencing ( Zhao et al, 2022 ; Petrin et al, 2023 ). Among these, 50 strains were from the northern region, and 52 were from the southern region.…”
Section: Methodsmentioning
confidence: 99%
“…High-throughput sequencing was performed with MiSeq Reagent kit v3, resulting in 251 bp long paired-end reads, or NextSeq High Output kit v2.5, resulting in 151 bp long paired end reads. Subsequent bioinformatics analyzes on raw reads were performed as previously described in Petrin et al ( 11 ).…”
Section: Methodsmentioning
confidence: 99%